Stable isotopic signatures for hydrogeochemical characterisation of ground water from Pondicherry to Nagapattinam, Tamil Nadu - Chidambaram, S.; Tirumelesh, K.; Prasanna, Mohan Viswanathan; Thilagavathi, R.; Pethaperumal, S.; Babu, G.; Paramaguru, P. (2015)
© Capital Publishing Company 2015.Groundwater recharge is a critical hydrological parameter. Identification of recharge zones and recharge estimates are essential to water resources management (Scanlon and Cook, 2002; Raju et al., 2006). In recent years, the overgrowing population and climate change are putting water resources under pressure all over the world. Sustainable management of aquifers to meet human and ecosystem needs will require protection of recharge areas and their augmentation (Reddy et al., 2000).